2D Modelling of turbulant transport of cohesive sediments in shallow reservoirs - De Villiers, J. W. L. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2006.